A new species of the genus Mesonemoura (Plecoptera: Nemouridae) and a key to the males of species known from China - Li, Weihai; Yang, Ding (Zootaxa, 2009)
A new species of the genus Mesonemoura, M. yulongana Li & Yang, sp. nov., is described from Yunnan Province, China. Its relationship with related species is discussed. A key to males of the 12 known species from China is provided.